AGAMA DALAM KEHIDUPAN INDIVIDU - Ahmad Taufik (Edification Journal : Pendidikan Agama Islam, 2019)
Religion as a form of human belief in something supernatural or supernatural turns out to be as if accompanying humans in the broad scope of life. Religion has values for human life as people per person and in relation to social life. Besides that religion also has an impact on everyday life. The influence of religion in an individual's life is to give inner stability, feeling of happiness, feeling of protection, a sense of success and satisfaction. This positive feeling will further be a motivator to do religion in the life of an individual besides being a motivation and ethical value is also hope.